A Meconium Aspiration Syndrome in Infants at Pranungklao Hospital - Sangaroon, Saowanee (Journal of Health Science of Thailand, 1995)
A retrospective study of meconium aspiration syndrome was conducted at Pranungklao Hospital during a 3-year period from January 1991 to December 1993. Nine infants (7 male and 2 female) with meconium aspiration syndrome were analysed. All of the infants were full-term with body weight over 2,500 grams. Three cases (33.33%) were delivered by cesarian section. Seven (77.77%) had low APGAR score at 5 minute. All were oral suctioned after delivery but 3 (33.33%) were oral suctioned and tracheal suctioned by using endotracheal tube. All (100%) needed oxygen therapy, 2 (22.22%) needed respirator supports and were died. 3 (33.33%) found abnormal of chest roentgenography. This study found that the factor related to the outcomes of treatment was low APGAR score at 5 minute. Appropiate antenatal and postnatal management guideline should be established and emphasized to decrease morbidity and mortality of meconium aspiration syndrome in infants.